The Influence of Interpersonal Skills of Working Students on Client Service Satisfaction in a Higher Educational Institution - Abejo, Chaldea G.; Adanza, Diosa Ruby Anne G.; Salvador, Haniza N.; Uy, Mary Niña J.; Indoc, Sheila Mae P.; Abiol, Michael Jere’ D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The research aimed to investigate the impact of working students' interpersonal skills on client service satisfaction in a higher education institution on Sabayle Street, Iligan City. The study, conducted in 2022, included 50 respondents to accomplish its objectives. Stratified random sampling was employed to assess the interpersonal skills of the respondents. The study's findings concluded that clients expressed a high level of satisfaction with the services they received, indicating a significant positive relationship between clients and working students. The research strongly recommended that both working students and their clients recognize and support this positive dynamic to strengthen their relationship further. Additionally, it encouraged the provision of constructive feedback on how working students interacted with their clients at St. Peter's College on Sabayle Street in Iligan City. In summary, this study shed light on the positive impact of working students' interpersonal skills on client service satisfaction. Acknowledging and nurturing this relationship was crucial for both parties involved, fostering an environment of mutual support and growth. Additionally, offering constructive feedback further enhances the quality of interactions between working students and clients in the academic setting.